2022
DOI: 10.1002/vetr.1630
|View full text |Cite
|
Sign up to set email alerts
|

Survival of dogs with pituitary‐dependent hyperadrenocorticism treated twice daily with low doses of trilostane

Abstract: Background Twice daily low trilostane doses have proven to be effective to manage canine Cushing's syndrome. However, survival and prognostic factors in dogs treated with this protocol have not been evaluated. The aim of the study was to evaluate survival and prognostic factors, including systolic blood pressure (SBP) at diagnosis, in dogs with pituitary‐dependent hypercortisolism (PDH) treated with low trilostane doses. Methods Medical records of 91 dogs newly diagnosed with PDH initially treated with 0.2–1.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
(102 reference statements)
0
9
0
Order By: Relevance
“…The median survival time for dogs with HC when treated with trilostane or mitotane has been reported to be 549 to 998 days. 55 , 56 , 57 , 58 Despite most dogs having persistent or worsening SMS, owners chose continued care. However, owners of 50% of the dogs in this study ultimately chose euthanasia because of persistent or worsening SMS, highlighting the impact that this condition can have on the dog's and owner's quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median survival time for dogs with HC when treated with trilostane or mitotane has been reported to be 549 to 998 days. 55 , 56 , 57 , 58 Despite most dogs having persistent or worsening SMS, owners chose continued care. However, owners of 50% of the dogs in this study ultimately chose euthanasia because of persistent or worsening SMS, highlighting the impact that this condition can have on the dog's and owner's quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The median survival time from initial diagnosis of SMS in the dogs included in this study was 963 days (range, 8‐1188 days). The median survival time for dogs with HC when treated with trilostane or mitotane has been reported to be 549 to 998 days 55‐58 . Despite most dogs having persistent or worsening SMS, owners chose continued care.…”
Section: Discussionmentioning
confidence: 99%
“…It is probable that the chronic inflammation caused by the saliva in contact with the soft tissues is the underlying cause of the sialocele calcification [21]. Calcifications have been widely reported in the veterinary literature and appear to be related to tumours, endocrinopathies and inflammatory lesions [33,34]. Tumours which can typically present calcification spots are pilomatricomas, benign follicular tumours located on the neck and trunk [33,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, muscle atrophy leads to exercise intolerance and motor function impairment, which are clinically relevant problems that affect a dog's quality of life. Furthermore, previous studies of dogs with HC have shown that muscle weakness or low body condition score, which are speculated to result from muscle atrophy, were associated with worse prognosis 13,14 . However, the evaluation of muscle atrophy in these studies was subjective, and no quantitative evaluation of muscle mass was conducted.…”
Section: Introductionmentioning
confidence: 98%